POTENTIAL OF ENDOFITING FUNGALE EXTRACT FROM THE LEAVES OF MANGO PARASITE (Dendrophthoe pentandra (L.) Miq) AS ANTIOXIDANTS - Dewi Qurrot 'Aini; Nour Athiroh Abdoes Sjakoer; Nurul Jadid Mubarakati (FAKULTAS PERTANIAN UNIVERSITAS BORNEO TARAKAN, 2023)
The importance of the presence of bioactive compounds that have the potential as antioxidants from various medicinal plants has become a topic that is often discussed by several researchers today. One of the higher-classification plants that potentially has antioxidant activity is the mango parasite (Dendrophthoe pentandra (L.) Miq), classified as a parasite of the Loranthaceae family. The use of specific endophytic fungi microbes from mango parasites of leaf tissue is expected to produce several bioactive compounds that act as antioxidants needed for large-scale production in a short time without excessive exploitation of nature. This primary research aims to determine the potential antioxidant activity of endophytic fungi extracts from the parasite of mango leaves Integrated Microbiology Laboratory and Halal Center of the Islamic University of Malang. Antioxidant testing using DPPH (2,2-diphenyl-1-picrylhydrazyl) free-radical capture of activity method. The results showed that KEDBM 1 (Aspergillus spp.) isolates had no potential antioxidant activity. While KEDBM 2 (Aspergillus spp.) isolate has the highest antioxidant potential with an IC50 value of 13.71 μg/ml and KEDBM 3 (Colletotrichum spp.) has a high potential as an antioxidant with IC50 of 36.29 μg/ml.Key words: antioxidant, mango balu, DPPH, endophyte